2014
DOI: 10.1038/srep07286
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling crucial biomechanical resilience of myelinated peripheral nerve fibres provided by the Schwann cell basal lamina and PMP22

Abstract: There is an urgent need for the research of the close and enigmatic relationship between nerve biomechanics and the development of neuropathies. Here we present a research strategy based on the application atomic force and confocal microscopy for simultaneous nerve biomechanics and integrity investigations. Using wild-type and hereditary neuropathy mouse models, we reveal surprising mechanical protection of peripheral nerves. Myelinated peripheral wild-type fibres promptly and fully recover from acute enormous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 25 publications
3
48
0
Order By: Relevance
“…We have recently shown that the average elastic Yong’s modulus of mature myelinated nerve fibers from mice is ∼ 20 kPa [13]. Here, embryonic DRG explants were exposed to substrates with elastic moduli of 1 kPa, 10 kPa and 20 kPa, referred to as soft, medium and hard, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that the average elastic Yong’s modulus of mature myelinated nerve fibers from mice is ∼ 20 kPa [13]. Here, embryonic DRG explants were exposed to substrates with elastic moduli of 1 kPa, 10 kPa and 20 kPa, referred to as soft, medium and hard, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We fabricated collagen substrates with stiffnesses of physiological relevance to the PNS by varying the collagen concentration using bespoke 3D‐printed moulds and the RAFT‐stabilization process. Two different collagen gradients (Lower and Higher) were created and compared to control plain RAFT‐stabilized gels with no gradient (Control).…”
Section: Resultsmentioning
confidence: 99%
“…Improved peripheral nerve repair strategies need to be developed and one of the emerging research avenues in tissue engineering is the study of cell–substrate interactions, which underpin conduits that support and guide neuronal regeneration. Recent studies have shown the importance of the mechanical environment within the peripheral nervous system during development and in pathological situations …”
Section: Introductionmentioning
confidence: 99%
“…The elastic modulus of each polymeric layer with the thicknesses as in the functional stack was determined by measuring the force-distance curve with an atomic force microscope (AFM) tip indenting the layer (Figure 1 f), accordingly to the routine proposed by Rosso et al [ 33 ] The data was fi tted to the Hertzian model [ 34 ] (see the Experimental Section for details) and the Young's modulus was determined by analyzing the slope of the linear part of the force-distance curve. We achieve a Young's modulus of the materials of 16.8 MPa for the capping polychloroprene layer, 4.5 MPa for the hydrogel layer, and 3.2 GPa for the stiff polyimide layer.…”
Section: Doi: 101002/adma201503696mentioning
confidence: 99%